Pengaruh Beban Kerja terhadap Turnover Intention yang Dimediasi oleh Kelelahan Kerja pada Karyawan Bagian Produksi - Nurul Hidayatin Nisa; Ayu Febriyanti; Fauziah Fauziah (Fakultas Ekonomi Universitas Islam 45, 2019)
A competitive business environment makes the company maximize employee performance with high work standards. This has a bad impact when the pressure that occurs makes employees feel the workload carried out exceeds their capacity (work overload). This should be watched out because it can result in work exhaustion and a desire to move. In this study, the industry is seen as a job that puts high pressure on employees. This study aims to examine whether there is an influence between workload on turnover intention which is mediated by work exhaustion in production section employees at PT. Alas Petala Makmur. The sampling technique uses proportionate stratified random sampling technique with a sample of 119 respondents. This study uses AMOS (Analysi Moment of Structure) software version 16.0 for windows. The results showed that workload does not directly affect turnover intention but workload affects work fatigue and work fatigue affects turnover intention and mediates work load against turnover intention.